Unusual Manifestation of Vitamin K Deficiency, Nodular Purpura: A Case Series - Sumedha Ballal; J. P Prathibha; Althea V. Pinto; Sanjanaa Srinivasa; Mary Augustine (Indian Dermatology Online Journal)
Vitamin K deficiency is a common entity in infancy characterized by bleeding from various sites, intracranial bleeding being the most commonly reported feature. Nodular purpura is an uncommon manifestation of vitamin K deficiency in infancy with a few reported cases in literature. We present four cases of infants presenting with nodular purpura as a manifestation of late-onset vitamin K deficiency bleeding (VKDB). All four children presented with asymptomatic bluish–gray nodules, along with symptoms of hepatic dysfunction. Coagulation profile was deranged in all four children and symptoms improved with the administration of parenteral Vitamin K. The case series details the clinical course, treatment response, and follow-up for each patient. To conclude, nodular purpura can be a rare presentation of late-onset VKDB. “Warning bleeds” of VKDB are known to precede dangerous intracranial bleeds. Late-onset VKDB cannot be prevented by routine neonatal vitamin K prophylaxis and requires repeated vitamin K treatments. The case series is an attempt to highlight the unusual manifestation of a bleeding disorder that can be easily prevented by early intervention.